2010
DOI: 10.1016/j.yhbeh.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Human disturbance alters endocrine and immune responses in the Galapagos marine iguana (Amblyrhynchus cristatus)

Abstract: Anthropogenic disturbance is a relevant and widespread facilitator of environmental change and there is clear evidence that it impacts natural populations. While population-level responses to major anthropogenic changes have been well studied, individual physiological responses to mild disturbance can be equally critical to the long-term survival of a species, yet they remain largely unexamined. The current study investigated the impact of seemingly low-level anthropogenic disturbance (ecotourism) on stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 59 publications
6
106
2
Order By: Relevance
“…While studies in another snake species found higher immune responses in females (Saad and Shoukrey 1988;Saad 1989), two studies in turtles reported no sex differences (Muñoz and De la Fuente 2001b; Keller et al 2006). On the other hand, the lack of sex differences in innate immunity parallels findings in water pythons (Ujvari and Madsen 2011) and marine iguanas (French et al 2010). Differential investment in immune function by the sexes is widespread in animals, although not universal, with females generally showing higher immune responses than males (Rolff 2002;Nunn et al 2009).…”
Section: Discussionsupporting
confidence: 58%
“…While studies in another snake species found higher immune responses in females (Saad and Shoukrey 1988;Saad 1989), two studies in turtles reported no sex differences (Muñoz and De la Fuente 2001b; Keller et al 2006). On the other hand, the lack of sex differences in innate immunity parallels findings in water pythons (Ujvari and Madsen 2011) and marine iguanas (French et al 2010). Differential investment in immune function by the sexes is widespread in animals, although not universal, with females generally showing higher immune responses than males (Rolff 2002;Nunn et al 2009).…”
Section: Discussionsupporting
confidence: 58%
“…Most studies on this subject in free-living species have been correlational and so there is limited support for a causal relationship between elevated glucocorticoids during stress and immunosuppression (Berger et al, 2005;Lindström et al, 2005;Matson et al, 2006;French et al, 2010;Kuhlman and Martin, 2010;Hopkins and Durant, 2011). By manipulating endogenous plasma CORT while controlling for the presence of the stressful stimulus, our results suggest a causal relationship between elevated plasma CORT during stress and the suppression of innate immunity.…”
Section: Stress-induced Suppression Of Innate Immune Constituentsmentioning
confidence: 60%
“…In addition, individuals residing in disturbed areas are exposed to a different array of stressors relative to their counterparts in non-disturbed areas. These stressors may impose substantial physiological constraints, such that fitness may be significantly affected in the long term, or individuals may be forced to alter their behavior and life history strategies (Ditchkoff et al 2006, French et al 2010.…”
Section: Discussionmentioning
confidence: 99%